Kesediaan pelajar tahun akhir fakulti pendidikan UTM menceburi bidang keusahawanan - Buntat, Yahya (2007)
This research was conducted in order to identify students’ preparation to be an entrepreneur in several aspects. This research highlighted the various contributing aspects such as curriculum, interest, motivation and attitude. 95 students form Civil, Electrical, Mechanical and Kemahiran Hidup (A/E/J/H) course in Faculty Of Education University Technology Malaysia were selected as respondents for this study. A set of questionnaire comprising 2 sections, section A on the respondent’s particulars and section B consisted statem ent on the research scope were used as research instrument. The reliability of the instrument is α = 0.96. Data were processed and analyzed by using SPSS (Statistical Package For Social Science) 15.0 for windows to obtain frequencies, percentages and means. Result showed that all the aspect was studied at high level. All of the aspects students were identified as critical factor in influencing students’ preparation to be an entrepreneur.